2017
DOI: 10.1002/jhbp.440
|View full text |Cite
|
Sign up to set email alerts
|

An opportunity in difficulty: Japan-Korea-Taiwan expert Delphi consensus on surgical difficulty during laparoscopic cholecystectomy

Abstract: Background We previously identified 25 intraoperative findings during laparoscopic cholecystectomy (LC) as potential indicators of surgical difficulty per nominal group technique. This study aimed to build a consensus among expert LC surgeons on the impact of each item on surgical difficulty. Methods Surgeons from Japan, Korea, and Taiwan (n = 554) participated in a Delphi process and graded the 25 items on a seven-stage scale (range, 0-6). Consensus was defined as (1) the interquartile range (IQR) of overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 29 publications
0
54
0
1
Order By: Relevance
“…AC progresses from edematous cholecystitis through necrotizing cholecystitis to sub-acute cholecystitis in about 10 days, and edematous phase, which is a phase before proceeding tight adhesion, lasts for 72 h after symptom onset [22]. Necrotizing cholecystitis is also reported to be one of the risk factor for difficult LC [23, 24]. Thus, the Tokyo Guidelines recommend early LC.…”
Section: Discussionmentioning
confidence: 99%
“…AC progresses from edematous cholecystitis through necrotizing cholecystitis to sub-acute cholecystitis in about 10 days, and edematous phase, which is a phase before proceeding tight adhesion, lasts for 72 h after symptom onset [22]. Necrotizing cholecystitis is also reported to be one of the risk factor for difficult LC [23, 24]. Thus, the Tokyo Guidelines recommend early LC.…”
Section: Discussionmentioning
confidence: 99%
“…For the past few years, we have been striving to define surgical difficulty during LC based on objective, intraoperative findings [17,18,45]. Although a universal grading system has yet to be defined, we have set a difficulty score per expert consensus [45].…”
Section: Discussionmentioning
confidence: 99%
“…Disappointingly, the number of BDI cases does not seem to have gone down over the years, despite the introduction of other safety measures such as intraoperative cholangiography [12], use of landmarks other than CVS [13,14], and efforts to facilitate surgical education [15,16]. BDI may also occur in difficult situations, particularly in acute cholecystitis (AC) [17,18]. A recent study demonstrated an increased risk of BDI according to the severity grade of AC per Tokyo Guidelines 13 [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Intra‐operative findings were systematically graded on a scale of 1–4 by the surgeon during the operation. The grading system represents a concise but simplified modification of intra‐operative factors known to be associated with the degree of difficulty of LC . Grades 1 and 2 were considered ‘straightforward’ operations, and grades 3 and 4 were considered ‘complicated’ operations as illustrated in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…A complex or prolonged operation may result from unexpected intra‐operative findings that cannot be dealt with by on‐call surgeons or trainees who do not have the requisite skills or experience. Severe inflammation around the gallbladder (GB) can make safe dissection difficult, and may increase the risk of both minor and major complications . When an early LC policy is adopted for patients with acute biliary presentations it would be helpful to predict the degree of operative difficulty.…”
Section: Introductionmentioning
confidence: 99%